An observational study of the occurrence of anxiety, depression and self-reported quality of life 2 years after myocardial infarction - Henriksson, Catrin; Wernroth, Mona-Lisa; Christersson, Christina (Journal of Cardiology and Cardiovascular Medicine, 2018)
Background: Patients with myocardial infarction (MI) often experience anxiety, depression and poor quality of life (QoL) compared with a normative population. Mood disturbances and QoL have been extensively investigated, but only a few studies have examined the long-term effects of MI on these complex phenomena. Aims: To examine the levels and associated predictors of anxiety, depression, and QoL in patients 2 years after MI. Methods: This was a single center, observational study of patients with MI (n=377, 22% women, median age 66 years). Two years after MI (2012-2014), the patients were asked to answer the Hospital Anxiety and Depression Scale (HADS) and EuroQol 5-dimension (EQ-5D-3L) questionnaires. Results: Most patients experienced neither anxiety (87%, 95% confidence interval [CI]: 83-90%) nor depression (94%, 95% CI: 92-97%) 2 years post-MI. Elderly patients experienced more depression than younger patients (p=0.003) and women had higher anxiety levels than men (p=0.009). Most patients had “no problems” with any of the EQ-5D-3L dimensions (72-98%), but 48% (95% CI: 43%-53%) self-reported at least “some problems” with pain/discomfort. In a multiple logistic regression model (EQ-5D-3L) higher age (p<0.001) and female sex (p<0.001) were associated with more pain/discomfort. Female sex (p=0.047) and prior MI (p=0.038) were associated with anxiety/depression. History of heart failure was associated with worse mobility (p=0.005) and problems with usual activities (p=0.006). The median total health status of the patients (EQ-VAS) was 78 (95% CI: 75-80)